Analysis of the Use of E-Court as An Electronic-Based Court Service in the Administration of Civil Judgment in Indonesia - Azmiy, Alifia Sabrina; Anggriani, Lulu; Pascal, Arya; Maulana, Defa Gustara; Nugraha, Ilham; Irfan, Muhammad; Siswajanthy, Farahdinny (Universitas PGRI Madiun, 2024)
A Technological advances have a broad impact on every aspect of people's lives, including the legal system, especially the e-court system which is a form of the government service system. The aim of the electronic justice system is to simplify the justice system by enabling online registration of cases, payments, summons and hearings. People had to waste time and energy traveling to and from court buildings before e-courts were available, making this service inefficient and ineffective. However, there are a number of obstacles to the use of E-Court, including lack of public outreach and education, limited human resources, and gaps in access to information and communication technology. Normative juridical research is the backbone of this research while also relying on secondary data. For this research, we also consulted secondary sources, such as government records and scientific publications, to gather information. The results found that the use of E-Court as a court service in Indonesia provides benefits including increased efficiency and effectiveness of justice, greater public trust in the justice system.